Thrombosed Aneurysm of the External Jugular Vein: A Rare Cause of Cervical Mass. Issue 1 (January 2016) - Neto, Tiago; Balhau, Rui; Coelho, Ligia; Pinto, Isabel; Correia-Sá, Inês; Silva, Álvaro
Abstract : Background: External jugular vein aneurysm is a rare condition with few cases described in the literature. Complications include thrombus formation, thrombophlebitis, pulmonary embolism, rupture, and cosmetic complaint. Methods and Results: The authors present a clinical case and treatment of thrombosed aneurysm of the external jugular vein in a 47-year-old man. Conclusions: Despite its rarity, external jugular vein aneurysm should be remembered in the differential diagnosis of a cervical mass. Surgical excision is indicated in symptomatic aneurysms and for aesthetic reasons. Excision eliminates the risk of complications and allows for histopathologic diagnosis.